Smoking and Opportunistic Infections Contribute to High Rates of Respiratory Symptoms Among HIV-Infected Smokers. (4th October 2017) - Hlatshwayo, Matifadza; Sahagun, Ageline; Atkinson, Jeffrey; Presti, Rachel
Abstract: Background: Due to improved treatment, aging and decreased infectious complications, chronic respiratory co-morbidities have become more prevalent among HIV-infected patients. Previous data suggests that COPD occurs at higher rates and earlier ages in this population. Additionally, some patients with HIV have been subject to opportunistic infections (OIs) that may cause damage to the lungs, also increasing their risk for chronic lung disease. All of these factors may lead to high rates of respiratory symptoms. For this reason, new methods of screening patients for respiratory symptoms are required. We used the St George's Respiratory Questionnaire (SGRQ) to assess respiratory symptoms in HIV infected smokers. Methods: Current smokers, HIV-positive and HIV-negative participants, over age 30 and with at least a 15 pack-year smoking history were enrolled. Pulmonary function tests were performed to assess for obstructive defect. SGRQ were administered and served as the primary source for symptom-based data. CT scans were performed to evaluate for underlying lung disease. All patients underwent basic demographic data as well as HIV disease specific information, including CD4 count, HIV viral load, and history of OI. Results: This study included 85 HIV-infected patients and 43 HIV-negative controls. HIV-infected patients had lower tobacco exposure than HIV-negative patients (26.7 vs 43.7 pack-years.) and were younger (49.9 vs 56.2). Despite this, symptom-based scores did not vary (26.9 ± 20.7 vs 28 ± 25.4, P > 0.05) between the 2 groups, suggesting symptomatology may be a result of complex interactions between smoking, HIV, and COPD. Within the HIV-infected population, SGRQ scores were found to be most associated with pack year. Those with prior OIs had higher SGRQ scores (41.1 ± 21.2 vs 27.2 ± 21.7, P  = 0.016). Conclusion: The SGRQ may be a potentially useful modality for assessing respiratory symptoms in PLWH who have known risk factors for COPD. Additionally, further long-term studies in the smoking, HIV-infected population, as well as in HIV patients with prior OIs, are needed in order obtain a better understanding of the specific risk factors that contribute to the respiratory symptoms and the development of chronic respiratory co-morbidities. Disclosures: J. Atkinson, INHALD: Investigator, Research grant; R. Presti, INHALD: Investigator, Research grant